METHODOLOGY OF USING MULTIMEDIA TOOLS IN TEACHING THE DUTOR INSTRUMENT - Babayeva, Maxfirabonu; Nurmatova, Mayya (International Conference on Science, Education & Law, 2026)
This article discusses the methodology for the effective use of multimedia tools in teaching the dutor instrument during music culture lessons in secondary schools. The study analyzes the issues of organizing the process of studying Uzbek national instruments, in particular the dutor, based on modern pedagogical technologies. The possibilities of developing students’ musical hearing, performance skills and creative activity through multimedia tools - audio and video recordings, interactive presentations, virtual lesson plans and digital notes are revealed. The article substantiates the pedagogical effectiveness of multimedia-based classes through experimental work